Legal Protections Analysis for Physical Assault Victims and Their Impact on Public Safety: Case Study of Judge's Decision Number 399/Pid.B/2020/PN Dps - Fairuz Zahra, Shalsabila Putri; Dina Mukti Yatulloh (Arkus, 2024)
Demolition is a criminal act that not only violates the human rights of victims, but also has a serious impact on the community's sense of security. This study aims to examine the legal protection provided to victims of demolition in Judge Decision Number 399/Pid.B/2020/PN Dps and its implications for public safety. This study uses a normative juridical method with a case study approach. Primary data is obtained from judges' decisions, while secondary data is collected from laws and regulations, legal literature, and previous research. Data analysis is carried out qualitatively with legal interpretation and argumentation techniques. The decision of Judge Number 399/Pid.B/2020/PN Dps shows that there are efforts to protect the law for victims of demolition through the provision of compensation and rehabilitation. However, this ruling has not fully reflected the more comprehensive aspect of restorative justice. The implication of this decision on public security is that there is still potential vulnerability and public distrust of law enforcement. Legal protection for victims of demolition needs to be strengthened with a more comprehensive restorative justice approach, involving the active participation of victims, perpetrators, and the community. The strengthening of legal protection is expected to increase public security and prevent similar crimes from occurring in the future.